Mining environmental liabilities: a potential source of metal contamination for freshwater ecosystems in Costa Rica - Rojas-Conejo, Johanna (2021)
Metal mining in Costa Rica, and use of toxic substances in this activity, has occasionally resulted in the negligent abandonment of waste structures containing significant amounts of toxic metals. These structures have been exposed to oxidation and weathering, resulting in the environmental release of metals, thus affecting the quality of the surrounding freshwater ecosystems. The objective of the investigation was to determine to what extent the abandoned mining liabilities in Líbano de Tilarán, Guanacaste, are a potential source of metal contamination for the waters, sediments and benthic macroinvertebrates of the San José and Cañas Rivers. The possible consequences for the environment associated with the presence of mining wastes were quantitatively and qualitatively assessed through the amounts of metals present in the wastes and leachate. Infiltration tests were carried out and a wet cell kinetic test allowed describing the processes and chemical reactions that are likely to occur in mining wastes during rain, associated with the loading of metals in leachate. The presence of pyrite (FeS2), which favors the acidification of the medium and the release of metals, was shown by X-ray diffraction tests on samples of the waste materials. The results show a high content of metals (37.8 tons of lead, 20.2 tons of arsenic and 0.4 tons of cadmium) from the total of ~106 000 tons in mining liabilities, the solubilization of these and other metals in an oxidizing acid medium (pH: 4.16, EC: 3620 µs / cm and ORP: 275 mV) during the dry-rainy season transition and an important load of metals (277 kg / month of zinc, 234 kg / month of magnesium, 165 kg / month of aluminum, 96.1 kg / month of iron, 2.68 kg / month of cadmium, 0.90 kg / month of arsenic and 0.22 kg / month of lead) in leachates arriving to the San José River in September. This investigation showed that the abandoned mining liabilities in Líbano are a potential source of metal contamination for the surrounding freshwater ecosystems.